Salivary and serum markers of angiogenesis in periodontitis in relation to smoking - DOĞAN, BAŞAK (SPRINGER HEIDELBERG, 2021)
Objective Angiogenesis is essential in maintenance of periodontal homeostasis, and it is regulated by growth factors and cytokines, including basic fibroblast growth factor (b-FGF), endoglin, platelet and endothelial cell adhesion molecule (PECAM-1), vascular endothelial growth factor (VEGF), soluble intercellular adhesion molecule-1 (sICAM-1), and soluble vascular cell adhesion molecule-1 (sVCAM-1). In this study, the salivary and serum concentrations of these angiogenesis-related proteins in relation to smoking and periodontitis were examined. Material and methods Full-mouth periodontal status together with unstimulated whole saliva and serum samples was collected from 78 individuals, including 40 periodontitis patients (20 smokers and 20 nonsmokers) and 38 periodontally healthy controls (20 smokers and 18 nonsmokers). The Luminex (R)-xMAP (TM) technique was used for protein analyses. Results Concentrations of all tested proteins in saliva as well as VEGF in serum were significantly higher in periodontitis patients than in healthy controls. In smokers, serum concentrations of endoglin (p = 0.017) and sICAM-1 (p = 0.001) were elevated in comparison to nonsmokers. After adjusting for smoking and gender, periodontitis associated significantly with salivary concentrations of b-FGF, PECAM-1, VEGF, sICAM-1, and sVCAM-1 (p < 0.01). Conclusion Taken together, salivary concentrations of b-FGF, PECAM-1, and VEGF associate with periodontitis. The suppressive effect of smoking on salivary marker levels is limited to periodontitis patients only.
Keywords: Basic fibroblast growth factor; Endoglin; Intercellular adhesion molecule-1; Platelet and endothelial cell adhesion molecule-1; Vascular cell adhesion molecule-1; Vascular endothelial growth factor; ENDOTHELIAL GROWTH-FACTOR; GINGIVAL CREVICULAR FLUID; ADHESION MOLECULE EXPRESSION; CIRCULATING ICAM-1; DISEASE; SMOKERS; PROGRESSION; NONSMOKERS; PECAM-1; TISSUES